Pengaruh Penerapan Enterprise Risk Management (COSO) Terhadap Nilai Perusahaan:Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI - Adie Pamungkas (Universitas Kristen Maranatha, 2019)
In the business world there are lot of uncertainties, every activity carried out or decisions taken always had risks, both small and large. The intelligence of managers, the technological sophistication used even the age of the company will not guarantee success. Today many old companies suddenly go bankrupt, including in Indonesia, the inability of companies to manage risk is the most fatal mistake. This study aims to determine the effect of the application of Enterprise risk management (COSO) on Corporate Value with the Price Book Value (PBV) method.The research method used is descriptive analysis method that is a method that describes what happens to the company based on the facts or events at the company. The author uses a purposive sampling method. The data used is secondary data sourced from annual reports from the 10 best manufacturing companies of the Forbes magazine listed on the Indonesia Stock Exchange for the period 2012-2015. The results of testing the data show that Enterprise risk management has an influence on Company Value. Based on the results of calculations So 4.186 t count> 2.02 t table. While the significant level is 0,000 <0,05. This indicates that ERM has a positive effect on Company Value. Keyword: Enterprise Risk Management: COSO: Corporate Value: Price Book Value (PBV)